Life Cycle Assessment of Power-to-Gas: Approaches, system variations and their environmental implications. (15th March 2017) - Zhang, Xiaojin; Bauer, Christian; Mutel, Christopher L.; Volkart, Kathrin
Graphical abstract: Highlights: Complete Life Cycle Assessment of Power-to-Gas with system variations. System expansion provides more meaningful results than subdivision. For Power-to-Hydrogen, the type of electricity supply is essential. For Power-to-Methane, source of CO2 and the approach applied can make a difference. Sensitivity analysis and impacts other than climate change were explored. Abstract: Electricity generation from intermittent renewable sources is expected to increase rapidly in the next decades. Integrating renewable energy requires energy storage during low-demand periods and potential conversion of surplus electricity into other energy carriers. Power-to-Gas (P2G) is a promising technology due to its potential to provide large-scale and long-term energy storage. However, this technology has many system variations, and their environmental performances need to be evaluated and compared with conventional technologies before large-scale deployment. In this paper, we investigate the environmental performance of P2G using Life Cycle Assessment (LCA), and mainly focus on the following three aspects: (1) discussion of differences as consequence of the approach applied for CO2 Capture and Utilization (CCU); (2) evaluation of technology variations including supply of electricity, alternative system processes (electrolysis technologies and CO2 sources), product gases (hydrogen and methane), and comparison of these P2G systems with conventional technologies, and (3) investigation of further environmental impacts of P2G in addition to the impact of global warming potential. We argue that in case of P2M, system expansion provides more meaningful results than subdivision for CCU, since it reflects the added value of CO2 utilization providing electricity or cement with low GHG intensity. The results of system variations show that P2G can, depending on electricity supply and CO2 source, reduce GHG emission compared to conventional gas production technologies, and that P2H has higher potential of emission reduction than P2M. Concerning other impact categories, P2H can have lower impacts than conventional hydrogen production, while P2M most often has higher impacts than using conventional natural gas.